The Effect of Short Movie toward Students’ Speaking Skill - Adillatunnisa' Adillatunnisa'; Masrul Masrul; Putri Asilestari (Journal of English Language and Education, 2021)
This experimental research was conducted at the tenth grade in SMA Muhammadiyah Bangkinang. This study aims to determine the effect of Short Movie on students' speaking skills. The research methodology was quasi experimental design. The sample of this research is class X IPA as the experimental class and X IPS as the control class. The experimental class consist of 21 students and the control class consisted of 24 students. This study uses a total sampling technique which includes all students in class X. The instrument used in this study is a speaking test. The data were analyzed using the SPSS 25 program. Based on the results of the study, the average score of students in the experimental class was 68.19 and 32.00 in the control class. Data analysis showed a significance (2-tailed) 0.000 0.05 it means Ha is accepted. It can be concluded that there is an effect on the use of Short Movie on students' speaking skills.